2010
DOI: 10.1007/s00253-010-3063-8
|View full text |Cite
|
Sign up to set email alerts
|

Acidithiobacillus thiooxidans secretome containing a newly described lipoprotein Licanantase enhances chalcopyrite bioleaching rate

Abstract: The nature of the mineral–bacteria interphase where electron and mass transfer processes occur is a key element of the bioleaching processes of sulfide minerals. This interphase is composed of proteins, metabolites, and other compounds embedded in extracellular polymeric substances mainly consisting of sugars and lipids (Gehrke et al., Appl Environ Microbiol 64(7):2743–2747, 1998). On this respect, despite Acidithiobacilli—a ubiquitous bacterial genera in bioleaching processes (Rawlings, Microb Cell Fact 4(1):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Culture purity and quantification was assessed from purified genomic DNA extracted by phenol:chloroform:isopropyl alcohol method by specific q‐PCR determinations with primers designed for specific 16S rRNA gene of At. thiooxidans DSM 17318 and total bacteria as proposed previously (Bobadilla et al, 2011) with comparable values for both determinations in the same order of magnitude.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Culture purity and quantification was assessed from purified genomic DNA extracted by phenol:chloroform:isopropyl alcohol method by specific q‐PCR determinations with primers designed for specific 16S rRNA gene of At. thiooxidans DSM 17318 and total bacteria as proposed previously (Bobadilla et al, 2011) with comparable values for both determinations in the same order of magnitude.…”
Section: Methodssupporting
confidence: 89%
“…At. thiooxidans DSM 17318 (strain patented by BioSigma ‘S.A.’ for its use in bioleaching processes) was grown in a 1 L bioreactor (Model BioFlo 110; New Brunswick, Edison, NJ) operated at 30°C and fed in batch cyclic mode (withdrawal of 500 mL of culture followed by replacement with the same volume of fresh medium every 48 h) with a based medium (pH 1.8) as described previously (Bobadilla et al, 2011) supplemented with 1% sulfur (99.5% purity; Sigma–Aldrich, St. Louis, MO). The culture was continuously aerated (1 L/min) and stirred (250 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…thiooxidans/At. ferrooxidans metasecretomes has been partially purified and its external addition slightly enhanced chalcopyrite bioleaching .…”
Section: Resultsmentioning
confidence: 99%
“…In leaching processes, iron oxidation and sulfur reduction by bioleaching microbes occur mainly in the extracellular space. In agreement with this, several proteomics studies revealed protein-associated molecules present in the extracellular polymeric substance (EPS) layers that are able to accumulate sulfur and enhance the bioleaching of metal sulphides [15]. Researchers determined the differential response in the proteome of the acidophilic halophile, Acidihalobacter prosperus DSM 14174 (strain V6) at low and high chloride ion level, to thus understand the mechanism of tolerance to high chloride ion stress in the presence of low pH [16].…”
Section: Introductionmentioning
confidence: 84%